Growth and Characterization of Non-Hydrazine Solution Processed Cu2(ZnSn)(SSe)4 Thin Films for Solar Cells - Gupta, Indu (My University, 2020)
Kesterite Cu2ZnSnS4 (CZTS) has emerged as a very promising absorber layer in thin film solar cells due to its earth abundant environmentally benign constituents and suitable optical properties. So far, the highest conversion efficiency of 12.6% for Se-alloyed CZTS (CZTSSe) films has been obtained by the solution process using hydrazine based slurry. Considering the explosive, hepatotoxic and carcinogenic nature of hydrazine, there have been wider research on facile synthesis of CZTS films from non-hydrazine non-toxic solutions. In this work, the CZTSSe films have been prepared from ethanol based homogeneous solutions using a direct solution coating route via dip coating. Firstly, ethanol, besides being an environmentally friendly solvent, solvates many common inorganic salts and can evaporate quickly (boiling point is ~78.5 °C) which can minimize residual carbon and/or oxygen related impurities in the films. Secondly, contrary to the approaches relying on fabricating thin films from CZTS particle-containing inks, homogeneous solution method offers several advantages such as better stoichiometric control (due to mixing at molecular-scale) and no requirement of pre-fabrication and stabilization of CZTS particles. In the CZTS device technology, the requirement of phase purity, dense microstructure with large grains, conformally deposited film thickness of ~ 1 m, appropriate band gap ( 1.0 - 1.5 eV) and electrical properties of the films are very critical for obtaining high efficiency of the devices. In the solution based approaches for semiconductor thin films, the film growth proceeds from the release of cations and anions from the precursor salts, and their subsequent reactions. The reaction pathway depends on various process parameters (such as temperature, precursor composition, deposition duration, complexing agent, etc.) and determines the eventual microstructure and phase of the films. In this thesis, while growing CZTS films from ethanol based solutions containing common metal salts, the influence of the process parameters has been investigated in detail and attempts were made to develop an understanding of the reaction pathway leading to the formation of sub-micrometer thick single phase kesterite CZTS films from the precursor solution via intermediate solid state binary and ternary compounds during deposition and the subsequent sulfurization/selenization treatment. While investigating the role of complexing agents, we found that the presence of monoethanolamine (MEA) - a routinely used complexing agent - in the initial stage of solution mixing, inhibits complete reduction (oxidation) of Cu2+ (Sn2+), which subsequently affected the reaction pathway resulting in undesirable secondary phases. On the other hand, the activation iii energy for the decomposition of the precursor complex was found to be smaller, surmounted in the early formation of the single phase CZTS in the absence of MEA. Another important aspect of growth of the CZTS thin films is the post-deposition high temperature annealing (HTA), which must be carefully controlled first to weaken the bonds in the organic-inorganic complexes, and then to allow reactions to yield the eventual films. We have studied the influencing mechanisms of phase evolution by employing ten possible HTA settings with elemental sulfur that includes systematic variations in ramp rate, sulfur source temperature and reaction temperature. Phase pure kesterite CZTS was found to have formed only in one instance, highlighting the crucial dependence of reaction path on the HTA setting. The proposed HTA strategy for reproducible growth of phase pure kesterite CZTS films is based on the geometry-controlled confinement of the sulfur vapor flux nearer to the reacting surface of the precursor film creating a sufficiently high partial pressure of sulfur that promoted growth of kesterite CZTS and prevented its decomposition reaction at elevated temperatures. The thickness of the films and the grain size was significantly improved with minimum process steps with an intuitive optimization of precursor solution concentration and the sulfurization and selenization ambience - amount of S and Se flakes, heat treatment duration and temperature. It was found that in just two dipping cycles from precursor solutions having 1.0 M CuCl2 solution direct solution coating followed by sulfurization at 500 C, phase pure kesterite CZTS films of ~850 nm thickness can be obtained. Additionally, in contrast to the reported bilayered structure (i.e., performance limiting small-grained bottom layer and large grained top layer), the resulting films exhibited a conformal microstructure with reasonably large grains. Selenization of the above-obtained phase pure CZTS films at 575 °C for 15 min with 1.5 gm of Se resulted in single phase CZTSSe thin films with Se/S+Se ratio of 0.68 and bandgap of 1.06 eV. These films having a thickness of 1.2 m exhibited a very compact and large-grained microstructure. Thus, in the given experimental setting, this presents a case of optimized condition for the formation of CZTSSe films for photovoltaic application. In order to complete the p-n junction for the solar cells, n-type CdS thin films were prepared from ammonia free solutions in the chemical bath deposition approach. The ammonia-free recipe to prepare the CdS films assumes importance in that it helps to reduce the overall toxicity of the wastage from the film deposition process. We have found that the properties of the films grown from ammonia-free solutions are very similar to those of the films grown from solutions with iv ammonia as reported in literature. The films were grown at different bath temperatures, namely at 40, 60 and 80 °C and the bath temperature dependence and scaling of surface roughness of the films were studied. From the series of the atomic force micrographs of films of varying deposition times, power spectral density and height-height correlation functions were evaluated, and roughness and growth exponents were determined. The surface width w(r,t) for small r exhibited power law scaling dependence on t, but differently at local and global scale, which is typical of anomalous scaling. We find that deposition at 40 C yielded films suitable for application in CZTS based devices. Solar cells in a typical structure of glass/Mo/CZTS/CdS/i:ZnO/ZnO:Al/Al were fabricated and a maximum efficiency of 0.49 % has been obtained. The main reason of the poor performance of the devices may be the low JSC and the very low fill-factor (FF). The low FF has been attributed to the high series resistance and low shunt resistance of the device, which originate from the poor microstructure, reactions at interfaces, and inappropriate electrical properties of the window layers. Further studies have been suggested to improve the performance of the devices.
PhD
Keywords: Thin films; Solar Cells; Solution processing; Kesterite